Speech text of signing ceremony memorandum of understanding between Universiti Teknologi MARA and Beijing Union University / Prof. Datuk Dr. Shahrin Sahib @ Sahibuddin - Sahib @ Sahibuddin, Shahrin (2023)
Alhamdulillah, praise be to Allah S.W.T. for the blessings bestowed upon us and the chance to assemble for another important undertaking for UiTM, especially for the Centre of Foundation Studies of UiTM. 2. A very warm welcome and Selamat Datang to all eminent guests to the Memorandum of Understanding (MoU) signing ceremony between Universiti Teknologi MARA (UiTM) and Beijing Union University (BUU).